O discurso do branco e para o branco: uma análise discursiva de rótulos e propagandas - Oliveira, Mirian Ribeiro de (2011)
ABSTRACT: This thesis aims to analyze labeling and advertising discourses as identity devices, curtailed by and submitted to racist ideology of color, techniques of subjectivity and objectivity that materialize in the power games of daily life. From this perspective, we discussed the mechanisms that determine a speech said to be true and normalizing, establishing attitudes and ways of being that discriminate by color, as well as criteria adopted for the selectivity of biased discursive formations that set standards of labeling, not for products only but also for people. Thus, labels and advertisements, from the universe of beauty and aesthetic devices, operate as the dominant identity that controls discursive strategies, aiming at the stay and preponderance of whiteness. This identity formation gained strength through a so called instrumental reason, reinforced by the logic of domination, established to neutralize the other, features of modernity. In contrast, the recurrence was caused by disruptions and historical displacements that place it in a world occupied by a decentered and changing subject who has no fixed identity, linked to the contemporaneity. A seemingly paradoxical subject that is also part of another discursive arena called culture of the mass media. It is from this place that the subject speaks and elects the image as a predominant category of speech. Thus, advertised labels and images are translated as a place of identity discourse productions. It is in this discursive space that the standard of whiteness gains evidence, being monitored and controlled by power relations. On the other hand, in order to ratify the circulation of power, it is necessary resistance which can also leak from the discursive space. So, to assess labeling and advertising discourses as identity devices, the French line discourse analysis was chosen as theoretical and methodological base with reference to studies of Pechêux and Foucault and other theorists who discuss the categories of racism color and identity. Under this bias, it became apparent that there is a veiled racism of color, seemingly naïve that gradually comes to life in the social environment. This veiled racism is activated by discursive mechanisms that construct the subject of contemporaneity, possessor of traces of modernity, submitted to a standard of identity, stereotype of beauty and aesthetics: the standard of whiteness.